Nonvisualized sentinel node on preoperative lymphoscintigraphy in primary cutaneous melanoma: an 11-year retrospective survey. Issue 5 (27th May 2023) - Pallara, Tiziano; Annovazzi, Alessio; Cristiani, Renzo; Vinci, Federica; Bertozzi, Ettore; Bonadies, Antonio; Romani, Claudia; Tedesco, Marinella; Bellei, Barbara; Papaccio, Federica; Caputo, Silvia; Cota, Carlo; et al.
Abstract : Background: Sentinel lymph node (SLN) biopsy in cutaneous melanoma patients evaluates the regional draining basin for occult micrometastatic disease. Occasionally, nonidentification of SLN impairs the acquisition of this important prognostic factor. Objectives: To investigate the outcomes of melanoma patients with negative lymphoscintigraphic findings and patients who underwent SLN biopsy from 2004 to 2015 ( n  = 1200) were retrospectively reviewed for tumor characteristics and clinical outcomes. Methods: Patients with nonvisualized lymph nodes (NV group) who underwent only preoperative lymphoscintigraphy were separated and compared with a cohort drawn from all melanoma patients who completed the surgical procedure within the same period (V group). Results: A negative lymphoscintigraphic scan was observed in 38 cases (3.2% of all patients). The NV group showed a significantly older age (median 66.0 vs. 48.3 years; P  < 0.0001). Head and neck melanomas were more frequent in the NV group compared to the control group (25.1 vs. 7.8%; P  = 0.009). Tumor characteristics such as ulceration and Breslow thickness do not influence the lymphoscintigraphy result. No differences were found in overall survival (OS) and disease-free survival (DFS) between the groups. Conclusions: The nonvisualization of regional lymph nodes by lymphoscintigraphy is more frequent in older patients with head and neck melanomas. From the clinical point of view, no specific recommendation emerged for patients' management because the nonvisualization of the SLN did not show a significant influence on DFS and OS rates. However, lack of knowledge of lymph node status suggests performing a tighter follow-up eventually by ultrasound evaluation of all potential lymph node drainage basins.